Efficacy of Metformin and Chemotherapeutic Agents on the Inhibition of Colony Formation and Shh/Gli1 Pathway: Metformin/Docetaxel Versus Metformin/5-Fluorouracil - Fatehi-Agdam, Maryam; Vatankhah, Mohammad Amin; Panahizadeh, Reza; Jeddi, Farhad; Najafzadeh, Nowruz (Drug Research, 2020)
Background Gastric cancer is a common gastrointestinal cancer characterized by poor prognosis and chemoresistance. Docetaxel and 5-fluorouracil (5-FU) are frequently used for the treatment of gastric cancer. Despite their potent anti-cancer effects, chemoresistance occurs in metastatic gastric cancer. Metformin, a popular anti-diabetic drug, has been proven to have potent anticancer effects on gastrointestinal cancers. Here, we aim to improve this chemotherapy agents’ efficacy by pretreatment with metformin.Methods The AGS gastric cancer cell line were pretreated with three different sub-toxic concentration of metformin and then treated with various concentrations of 5-FU and docetaxel.The anticancer effects of the combination of metformin with the chemotherapy agents were determined using clonogenic assay and DAPi staining. We used real-time PCR to evaluate Gli1, Gli2, and TWIST1 mRNA expression levels in the gastric cancer cells. Also, the expression of the Shh protein was assessed using immunocytochemistry.Results Here, we found that metformin sensitized the gastric cancer cells to chemotherapy. The combination treatments were more effective in reducing the number of cancer colonies compared to 5-FU or docetaxel alone. The combination of metformin with 5-FU or docetaxel significantly reduced the number of cells expressing the Shh protein compared to the 5-FU alone or docetaxel alone. Interestingly, we found that the combination of metformin with docetaxel significantly down-regulated the mRNA levels of Gli1, Gli2, and TWIST1 in the AGS gastric cancer cell line compared to docetaxel alone.Conclusion Overall, our data strongly support an important role for metformin as an enhancer of the efficacy of chemotherapeutic agents against gastric cancer.
Keywords: metformin; docetaxel; 5-fluorouracil; Shh; Gli1; Gli2; gastric cancer